The Science of Learning Principles of Educational Thinking Based on the Teaching Practice - Wen, Hanjiang (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book systematically summarizes the author's more than 30 years of experience in teaching reform and educational research. The book is divided into three parts. Part I focuses on the comprehensiveness of thinking and the relationship between the coordinated development of thinking and the overall development of human beings. Part II and Part III mainly discuss the six basic principles of learning and thinking: the principle of the working memory of thinking, the principle of learning transfer, the principle of the basic process of learning, the principle of multi-level development of ability, the principle of sustainable development of learning, and the principle of subjectivity of learning. This book features the rules and characteristics of student learning with a student-centered approach, which can help teachers and educational researchers to better understand students and provide theoretical guidance for students' all-round development.
Chapter 1. The Comprehensiveness of Thinking -- Chapter 2. The Comprehensiveness of Thinking and the All-round Development of HumanBeings -- Chapter 4. Modern Educational Media--A Carrier of Coordinated Development of Thinking -- Chapter 5. Thinking and Memory -- Chapter 6. Thinking and Learning Transfer -- Chapter 7. Learning and Human Development -- Chapter 8. Sustainable Development of Thinking and Learning$1!+:(BResolving Difficulties in Learning -- Chapter 9. Subjectivity of Learning. .s
Keywords: Educational psychology; Learning, Psychology of; Study Skills; Educational Psychology; Learning Theory; Instructional Theory; Study and Learning Skills